Exploring the Diversity Within the Genus Francisella – An Integrated Pan-Genome and Genome-Mining Approach - Kumar, Rajender; Bröms, Jeanette E.; Sjöstedt, Anders (Frontiers in Microbiology, 2020)
Pan-genome analysis is a powerful method to explore genomic heterogeneity and diversity of bacterial species. Here we present a pan-genome analysis of the genus Francisella, comprising a dataset of 63 genomes and encompassing clinical as well as environmental isolates from distinct geographic locations. To determine the evolutionary relationship within the genus, we performed phylogenetic whole-genome studies utilizing the average nucleotide identity, average amino acid identity, core genes and non-recombinant loci markers. Based on the analyses, the phylogenetic trees obtained identified two distinct clades, A and B and a diverse cluster designated C. The sizes of the pan-, core-, cloud-, and shell-genomes of Francisella were estimated and compared to those of two other facultative intracellular pathogens, Legionella and Piscirickettsia. Francisella had the smallest core-genome, 692 genes, compared to 886 and 1,732 genes for Legionella and Piscirickettsia respectively, while the pan-genome of Legionella was more than twice the size of that of the other two genera. Also, the composition of the Francisella Type VI secretion system (T6SS) was analyzed. Distinct differences in the gene content of the T6SS were identified. In silico approaches performed to identify putative substrates of these systems revealed potential effectors targeting the cell wall, inner membrane, cellular nucleic acids as well as proteins, thus constituting attractive targets for site-directed mutagenesis. The comparative analysis performed here provides a comprehensive basis for the assessment of the phylogenomic relationship of members of the genus Francisella and for the identification of putative T6SS virulence traits.